Peran Satuan Sabhara Polres Deli Serdang dalam Menjaga Keamanan dan Ketertiban Masyarakat Berdasarkan Undang-Undang Nomor 2 Tahun 2002 Tentang Kepolisian Negara Republik Indonesia - Panusunan Siregar; Muhammad Hizbullah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The Samapta Bhayangkara Unit (Sabhara) serves as the operational frontline of the Resort Police in maintaining public security and order. In the jurisdiction of Deli Serdang Resort Police, security challenges have increased, as indicated by an average annual growth in criminal offenses of 12.8% during 2020–2024 and a 65.4% annual increase in cybercrime. This study aims to analyze the role of the Sabhara Unit of Deli Serdang Resort Police in maintaining public security and order based on Law Number 2 of 2002 concerning the Indonesian National Police. The study employs a normative-empirical legal method, with primary data obtained through in-depth interviews with seven informants selected using purposive sampling, consisting of Sabhara officials and personnel, community leaders, and legal academics. Data were analyzed using a descriptive qualitative approach with source triangulation. The findings indicate that Sabhara has performed preventive, repressive, and community empowerment functions in accordance with Articles 13 and 14 of Law Number 2 of 2002; however, gaps remain between standards and implementation, particularly in emergency response times and case resolution. Effectiveness is also constrained by personnel shortages, limited facilities and infrastructure, low community participation, and suboptimal inter-agency coordination. Optimization requires the integration of community policing, intelligence-led policing, and problem-oriented policing, along with strengthening personnel capacity, operational facilities, procedures, and community partnerships.